Studies Concerned with the Structure and Synthesis of the Anti‐viral Tropolone Glycoside Liriosmaside A - Qi Chen; Yaping Zhan; Michael G. Gardiner; Zeinab G. Khalil; Amila A. Dewa; Thulasi Sritharan; Robert J. Capon; Ping Lan; Shen Tan; Martin G. Banwell (ChemistryOpen)
Abstract A bromotropone corresponding to the agylcone of the glycosylated sesquiterpenoid natural product liriosmaside A has been prepared over ten steps and in a fully regio‐controlled manner through the gem‐dibromocyclopropane‐mediated ring‐expansion of a readily accessible decalenone. A Pd[0]‐mediated glucosylation reaction applied to this bromotropone afforded a product mixture from which an enantiomerically pure cross‐coupling product could be obtained and its structure confirmed through single‐crystal X‐ray analysis of a derivative. Various (unsuccessful) attempts are described to selectively acylate the last compound and thereby install the 3‐hydroxy‐3‐methylglutaric acid or HMGA‐containing side chain of the title natural product. A literature survey of other natural products embodying the HMGA motif suggest that liriosmaside A and its co‐metabolite liriosmaside B could be S‐configured at C3”. The evaluation of the glucosylated tropone in a series of anti‐bacterial, anti‐fungal and cytotoxicity assays reveals that it is inactive in all of these and so emphasizing the prospect that this and related troponoids, including the natural products liriosmaside A and B, can serve as useful models for new anti‐viral agents.